Analysis of the cold chain in the hospital pharmacy: case of the university hospital centre in Morocco. (16th October 2019) - Tamir, Manal; Chiheb, Raddouane; Ouzayd, Fatima; Mansouri, Hajar
The drugs market has experienced lately a significant diversification in the types of medical treatments and some of them use medicines that require a mode of preservation under specific temperature ranges. In fact, the purpose of the drugs cold chain is to guarantee the respect of these temperature ranges throughout the drug circuit, namely transport and storage until the administration to patients. Actually, a large number of healthcare organisations suffer from the defectiveness of the cold chain products following the non-compliance of the required temperatures. Sometimes, the defect is not detected due to temperature traceability problems and the products can be administrated to the patients and have serious effects on their health. The main purpose of this paper is then to analyse the cold chain in the hospital pharmacy. The analysis will concern the general cartography proposed in this paper, namely the different actors and procedures of this chain. Finally, the failures of the drugs cold chain in the Moroccan regulation will be analysed and thus will be proposed the different orientations that the government must adopt in order to follow the progress of the international regulation.